2016
DOI: 10.1016/j.jcf.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography detects structural abnormalitiesof the nasal mucosa in patients with cystic fibrosis

Abstract: OCT detected mucosal changes associated with upper airway inflammation and response to antibiotic therapy in CF patients. OCT may be a useful tool for quantitative in vivo assessment of structural changes of the airway mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…In this context, a previous study indicated MRI may constitute an attractive tool for sensitive detection and non‐invasive monitoring of characteristic structural abnormalities of upper airways in children with CF . This notion is supported by preliminary studies conducted at our CF center demonstrating that MRI is sensitive to detect mucosal thickening in the paranasal sinuses even in infants and preschool children with CF (Fig. ).…”
Section: Mri For Monitoring Of Upper Airways Disease In Cfsupporting
confidence: 54%
See 1 more Smart Citation
“…In this context, a previous study indicated MRI may constitute an attractive tool for sensitive detection and non‐invasive monitoring of characteristic structural abnormalities of upper airways in children with CF . This notion is supported by preliminary studies conducted at our CF center demonstrating that MRI is sensitive to detect mucosal thickening in the paranasal sinuses even in infants and preschool children with CF (Fig. ).…”
Section: Mri For Monitoring Of Upper Airways Disease In Cfsupporting
confidence: 54%
“…In addition to lower airways disease, CFTR dysfunction causes chronic mucoobstructive disease of the upper airways characterized by mucus retention, infection and inflammation in the paranasal sinuses, and nasal cavity, often accompanied by the development of nasal polyps that may aggravate local mucociliary dysfunction and airflow obstruction Clinically, CF upper airways disease presents as chronic rhinosinusitis that is almost invariably present from early childhood . Compared to our current understanding of early lung disease, little is known about the onset and spontaneous progression of upper airways disease in children with CF.…”
Section: Mri For Monitoring Of Upper Airways Disease In Cfmentioning
confidence: 99%
“…In addition to these lab-based future directions, data generated about injury and regeneration to ciliated surfaces provides further motivation to the ongoing development of endoscopic/bronchoscopic in vivo OCT technologies (e.g. 26 , 27 ) for the potential longitudinal imaging of the injured tracheal mucosa in the ICU. In conclusion, utilizing multi-contrast OCT allows a multi-faceted investigation of injury to the ciliated epithelium by combining (a) PTV for a quantitative flow analysis with (b) 3D rendered speckle-variance imaging for visualization of ciliary patches.…”
Section: Discussionmentioning
confidence: 99%
“…A few ex vivo studies reported on the application of OCT for analysing wall degradation in aortic aneurysms [RVBR*14, OPW*16]. The dynamic motion of the inner vessel wall has been related to the underlying pulsatile flow [LDE14, KPG*16a].…”
Section: Flow Data Generation Pipelinementioning
confidence: 99%